Periodicity of the population size of an age-dependent model with a dominant age class by means of impulsive perturbations - Covačev, Valery (Zielona Góra: Uniwersytet Zielonogórski)
For an age-dependent model with a dominant age class an ?-periodic regime the population size is sought by means of impulsive perturbations. For both noncritical and critical cases of first order the problem is reduced to operator systems solvable by a convergent simple iteration method.
Keywords: population dynamics; age-dependent model; periodic solutions; nonlinear delay equations